PERAN GURU PPKn SEBAGAI ROLE MODEL DALAM MENGATASI KECANDUAN PENGGUNAAN GAWAI PADA SISWA KELAS VIII DI SMP NEGERI 024 SIHONONGAN - Mikael Sinambela, San; Siagian, Liber; Batubara, Abdinur; Yunita, Sri; Anastasya Sihaloho, Oksari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The increasing use of gadgets among students is causing various negative impacts, which poses a challenge for Civics and Citizenship Education teachers in addressing this issue. This study aims to determine the role of PPKn teachers as role models in addressing gadget addiction among eighth-grade students at SMP Negeri 024 Sihonongan. The research method used in this study is a qualitative method with a descriptive approach. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis was then conducted using data reduction, data presentation, and conclusion drawing. The results indicate that PPKn teachers at SMP Negeri 024 Sihonongan play a crucial role in addressing the problem of gadget use among students, manifested through their roles as role models, inspirators, motivators, dynamic facilitators, and evaluators. Factors influencing gadget addiction include internal factors, such as students' low self-control and the desire for instant gratification through social media, as well as external factors such as peer influence and lack of parental supervision at home. However, the active role of teachers and school support can offset these negative influences, enabling students to maintain a positive attitude toward using technology in today's digital age.